HUBUNGAN PELAYANAN KOMUNIKASI DAN EDUKASI PERAWAT DENGAN KEPUASAN PASIEN DI RS MEDIROSSA CIKARANG - Fatmayanti, Sri Ayu; Asmirajanti, Mira; Setiawati (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Background: Nurses are the spearhead of patient recovery while in the hospital, providing good service through good communication and education so that patients feel satisfactory service. One effort to improve patient and family satisfaction is to implement nurse communication and education while patients are hospitalized. Patient satisfaction is one level of achievement of acceptance and response to health services in the form of communication, if nurses do not communicate well it will cause dissatisfaction in patients and families. Objective: To analyze the relationship between nurse communication and education and satisfaction at Medirossa Cikarang Hospital. The object of this study was inpatients at Medirossa Cikarang Hospital. The independent variable in this study was the Communication and Education services of nurses at Medirossa Cikarang Hospital and the dependent variable was patient satisfaction at Meddirossa Cikarang Hospital. Method: The research design used a cross-sectional method. The population of this study was all patients undergoing treatment in the inpatient room for >4 days at Medirossa Cikarang Hospital. The research was carried out from May to July 2023. The data collection technique was total sampling with a sample size of 141 respondents. Results: This study is based on the characteristics of respondents aged 46-55 years, namely 34 respondents (24.1%). The gender of the respondents is male, namely 85 respondents (60.3%), high school graduates, namely 71 respondents (50.4%), respondents as private workers as many as 45 respondents (31.9%). Communication and education of nurses to patients were found to be appropriate as many as 72 respondents (51.1%). Patient satisfaction was found to be satisfactory as many as 83 respondents (58.9%). Conclusion: There is a relationship between communication and education of nurses with patient satisfaction at Medirossa Cikarang Hospital with p value < 0,001. The results of this study indicate that there is a significant relationship between therapeutic communication and patient satisfaction levels.